PENGUATAN AQIDAH ASWAJA AN-NAHDHIYAH MELALUI TRADISI SEKATEN DI MASYARAKAT JAWA - Ma'arif, A. Samsul; Azizah, Ma’rufatul; Laillatul Fitri, Izzah; Amalia, Kharisma (An Nahdhoh Jurnal Kajian Islam Aswaja, 2024)
This article describes the richness of Indonesian culture as reflected in the diversity of natural resources, people, tribes, languages ​​and traditions. The focus is on the importance of traditional ceremonies as an integral part of people's lives, even though they are threatened with extinction if they lose their relevance. This research highlights the role of hereditary rules in preserving traditional ceremonies as well as the cultural mix between Islam and local traditions, as seen in the Sekaten ceremony. By examining the origins and purpose of the Sekaten ceremony, this article illustrates how Indonesia's cultural diversity creates a unique cultural heritage, combining elements of local culture with Islamic teachings.